The Structure of the Candida albicans Ess1 Prolyl Isomerase Reveals a Well-Ordered Linker that Restricts Domain Mobility(,) - Li, Zhong (Biochemistry, 2005)
Ess1 is a peptidyl-prolyl cis/trans isomerase (PPIase) that binds to the carboxy-terminal domain (CTD) of RNA polymerase II. Ess1 is thought to function by inducing conformational changes in the CTD that control the assembly of cofactor complexes on the transcription unit. Ess1 (also called Pin1) is highly conserved throughout the eukaryotic kingdom and is required for growth in some species, including the human fungal pathogen Candida albicans. Here we report the crystal structure of the C. albicans Ess1 protein, determined at 1.6 Å resolution. The structure reveals two domains, the WW and the isomerase domain, that have conformations essentially identical to those of human Pin1. However, the linker region that joins the two domains is quite different. In human Pin1, this linker is short and flexible, and part of it is unstructured. In contrast, the fungal Ess1 linker is highly ordered and contains a long α-helix. This structure results in a rigid juxtaposition of the WW and isomerase domains, in an orientation that is distinct from that observed in Pin1, and that eliminates a hydrophobic pocket between the domains that was implicated as the main substrate recognition site. These differences suggest distinct modes of interaction with long substrate molecules, such as the CTD of RNA polymerase II. We also show that C. albicans ess1(−) mutants are attenuated for in vivo survival in mice. Together, these results suggest that CaEss1 might constitute a useful antifungal drug target, and that structural differences between the fungal and human enzymes could be exploited for drug design.